Psychological, physiological and biochemical indicators of female professional basketball players and ski runners - I. Garnov; N. Varlamova; N. Potolitsyna; T. Loginova; E. Boyko (National Electronic Information Consortium (NEICON), 2020)
Objective: comparison of psychological, physiological and biochemical markers in female basketball players and ski runners. Materials and methods: we investigated 8 female basketball players and 12 ski runners. For this we used questionnaire «Recovery-Stress Questionnaire for Athletes», maximal bicycle ergometer endurance exercise test and biochemical analysis of venous blood. Results: we showed that female basketball players had, in comparison with ski runners, higher levels of sports stress, injury susceptibility - but also had higher self-efficacy values. Basketball players had higher average height, body mass and percentage of body fat, and higher oxygen pulse at rest. At the same time, they had lower efficacy and maximal oxygen consumption in maximal bicycle ergometer endurance exercise test. Female basketball players had lower plasma aspartate aminotransferase and total protein levels. Conclusions: we conclude that observed differences between female basketball players and ski runners were caused by differences in the initial selection criteria for basketball and ski running. Those initial dissimilarities were further reinforced by differences in typical physical tasks and demands, specific for their respective sports. Training regimens and other factors of the preparatory process also added to the differences observed between groups.